MASALAH SOSIAL DAN KONFLIK MASYARAKAT ADAT PAPUA DENGAN PT FREEPORT INDONESIA - Nita Safitri (Universitas Medan Area, 2016)
Prolonged conflict between the indigenous people of Papua and PT. Freeport Indonesia should receive serious attention from the government. Not only casualties property but also be a “thorn in the flesh” in the way of national and state, because this conflict into the international spotlight and influence overseas investor for security reason that are not guaranteed. The conflict has taken approximately 40 years old, there must be something wrong in the stage of completion. Settlement with guns and violence is not the right solution even sharpen the conflict even during the year 2009 has been approximately 50 times the clash of indigenous Papuans with PT. Freeport Indonesia and the government until 2010 even clashes are still on going. Need cultural wisdom in seeing social problems and attention to policy and development culture that framed the conflict can be ended.